ANALISIS PENENTUAN NILAI PASAR WAJAR SAHAM PT. BANK DANAMON INDONESIA Tbk. PASCA KEBIJAKAN RIGHT ISSUE 31 DESEMBER 2012 - , Ispindar Zen; , Dr. Muhammad Edhie Purnawan, M.A., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study has the objective is to estimate the intrinsic value of the shares of Bank Danamon Indonesia Tbk. policy post-rights issue by using the income approach is to apply the method of discounted cash flows (discounted cash flow) to the model to the company's free cash flow (free cash flow to the firm) and market approach (relative valuation). The data used consists of financial statements of Bank Danamon Indonesia Tbk. past three years from 2009 through 2011. Discounted cash flow method of analysis is done by: projection of financial statements (balance sheet and income statement), the projected free cash flow to firm (FCFF), determination of the discount rate, the determination of terminal value, and determining the estimated value of the company. Analysis of the market approach (relative valuation) begins with a search for comparable companies in similar lines of business, choose and assign the appropriate multiple or ratio of comparable companies. This multiple is used to convert the book value of the relevant variables of Bank Danamon Indonesia Tbk. be the estimated market value. Multiple used is: PER (Price Earnings Ratio), PBV (Price to Book Value), and P/S (Price to SalesRatio). The results using the discounted cash flow estimate of intrinsic value of shares acquired Bank Danamon Indonesia Tbk. per December 31, 2012 amounted to Rp6.269,85 while the estimated value of the shares based on relative valuation is Rp4.694,11 In this study, the reconciliation of the estimated intrinsic value or fair value of the shares of Bank Danamon Indonesia Tbk. determined by giving equal weight between the two approaches so that the obtained value of Rp5.481,98